Pengaruh Ketepatan Waktu terhadap Loyalitas Pelanggan PT. Fajar Citra Mandiri - Supandi, Agus; Johan, Ria Susanti (Sosio e-Kons, 2023)
The research aims to analyze and test the truth of the hypothesis regarding the effect of timeliness on PT customer loyalty. Fajar Citra Mandiri. The research was carried out using quantitative methods using simple linear regression calculation techniques. The population in this research is customers of PT. Fajar Citra Mandiri with a sample size of 70 people, with the sampling technique used, namely non-probability sampling. The research instrument used was the results of a questionnaire distributed and filled in by customers with 40 questions. Based on the calculations carried out, the results obtained show that in a simple linear analysis there is a significant relationship between the effect of timeliness on customer loyalty. In this analysis, the constant (a) has a value of 18.73 and the regression coefficient (b) has a value of 0.672. This means that every 1% increase in the effect of timeliness will result in an increase in customer loyalty of 67%. This was obtained based on the results of calculating the regression coefficient (b), which shows a significant level of influence between the variables Influence of Timeliness and Customer Loyalty. In addition, the results of the product moment coefficient analysis show that the coefficient value of 0.809 obtained can be categorized as a very strong level of influence, in accordance with the correlation coefficient interpretation guidelines. This means that there is a very strong relationship between the influence of timeliness (X) and customer loyalty (Y) at PT Fajar Citra Mandiri.